PENGEMBANGAN INTERACTIVE E-BOOK BIDANG ASESMEN BAHASA UNTUK MENGEMBANGKAN KOMPETENSI DAN KEMANDIRIAN MAHASISWA PROGRAM PENDIDIKAN BAHASA - Sri Wahyuni (LITERA, 2014)
This study aims to produce an interactive electronic book (e-book) model for language assessment to develop the competency and autonomy of the students of the Indonesian language study program. The study employed a research and development procedure consisting of: a preliminary study, planning, and product development. The results of the study are as follows. First, the developed interactive e-book package consists of Lecturer’s Manual, Student’s Manual, and an interactive e-book on language assessment. Second, the results of the validation by the learning multimedia expert show that in general the product is appropriate (85%). Third, according to the subject matter expert, the contents of the product are very appropriate (94%). Fourth, the individual validation shows thatin general the students consider the product very good (90%). Fifth, the class validation shows that there is a significant difference between the pretest score and the posttest score. Therefore, the developed interactive e-book is effective to be used in language assessment learning.